2015
DOI: 10.3390/ma8073831
|View full text |Cite
|
Sign up to set email alerts
|

A Bone Sample Containing a Bone Graft Substitute Analyzed by Correlating Density Information Obtained by X-ray Micro Tomography with Compositional Information Obtained by Raman Microscopy

Abstract: The ability of bone graft substitutes to promote new bone formation has been increasingly used in the medical field to repair skeletal defects or to replace missing bone in a broad range of applications in dentistry and orthopedics. A common way to assess such materials is via micro computed tomography (µ-CT), through the density information content provided by the absorption of X-rays. Information on the chemical composition of a material can be obtained via Raman spectroscopy. By investigating a bone sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The use of animal models seems to be a required step in testing new bone regeneration materials [96]. The in vivo applicability of bioengineered 3D constructs [97] and bone graft substitutes is usually evaluated in animals models as rats, rabbits, mini pigs bone defects, and applications are recorded in dentistry [98][99][100][101][102] as in MFS [103][104][105]. Mainly, the biomaterials and bone grafts investigated for tissue engineering applications are:…”
Section: Biomaterials and Bone Tissue Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of animal models seems to be a required step in testing new bone regeneration materials [96]. The in vivo applicability of bioengineered 3D constructs [97] and bone graft substitutes is usually evaluated in animals models as rats, rabbits, mini pigs bone defects, and applications are recorded in dentistry [98][99][100][101][102] as in MFS [103][104][105]. Mainly, the biomaterials and bone grafts investigated for tissue engineering applications are:…”
Section: Biomaterials and Bone Tissue Regenerationmentioning
confidence: 99%
“…Raman spectroscopic imaging, a laser-based microscopic device, was applied with micro-CT to examine bone samples and Charwat-Pessler et al [98] reported that the two different imaging techniques provide complementary and mutually supportive information.…”
Section: Micro-ct Analysis Combined With Other Techniques or Technolomentioning
confidence: 99%